Influences of Yogurt with Functional Ingredients from Various Sources That Help Treat Leaky Gut on Intestinal Barrier Dysfunction in Caco-2 Cells - Ricardo S. Aleman; Ryan Page; Roberto Cedillos; Ismael Montero-Fernández; Jhunior Abraham Marcia Fuentes; Douglas W. Olson; Kayanush Aryana (MDPI AG, 2023)
The impact of yogurts made with starter culture bacteria (L. bulgaricus and S. thermophilus) and supplemented with ingredients (maitake mushrooms, quercetin, L-glutamine, slippery elm bark, licorice root, N-acetyl-D-glucosamine, zinc orotate, and marshmallow root) that can help treat leaky gut were investigated using the Caco-2 cell monolayer as a measure of intestinal barrier dysfunction. Milk from the same source was equally dispersed into nine pails, and the eight ingredients were randomly allocated to the eight pails. The control had no ingredients. The Caco-2 cells were treated with isoflavone genistein (negative control) and growth media (positive control). Inflammation was stimulated using an inflammatory cocktail of cytokines (interferon-γ, tumor necrosis factor-α, and interleukin-1β) and lipopolysaccharide. The yogurt without ingredients (control yogurt) was compared to the yogurt treatments (yogurts with ingredients) that help treat leaky gut. Transepithelial electrical resistance (TEER) and paracellular permeability were measured to evaluate the integrity of the Caco-2 monolayer. Transmission electron microscopy (TEM), immunofluorescence microscopy (IM), and real-time quantitative polymerase chain reaction (RTQPCR) were applied to measure the integrity of tight junction proteins. The yogurts were subjected to gastric and intestinal digestion, and TEER was recorded. Ferrous ion chelating activity, ferric reducing potential, and DPPH radical scavenging were also examined to determine the yogurts' antioxidant capacity. Yogurt with quercetin and marshmallow root improved the antioxidant activity and TEER and had the lowest permeability in fluorescein isothiocyanate (FITC)-dextran and Lucifer yellow flux among the yogurt samples. TEM, IM, and RTQPCR revealed that yogurt enhanced tight junction proteins' localization and gene expression. Intestinal digestion of the yogurt negatively impacted inflammation-induced Caco-2 barrier dysfunction, while yogurt with quercetin, marshmallow root, maitake mushroom, and licorice root had the highest TEER values compared to the control yogurt. Yogurt fortification with quercetin, marshmallow root, maitake mushroom, and licorice root may improve functionality when dealing with intestinal barrier dysfunction.